Evaluation of soil quality identified by local farmers in Mai-Negus catchment, northern Ethiopia - Brhane Tesfahunegn, Gebrayesus; Tamene, Lulseged D.; Vlek, Paul L.G. (Elsevier, 2011)
Though soil quality (SQ) degradation is a serious challenge to national food security, little information is available that evaluate farmer SQ knowledge vis-à-vis scientific knowledge at catchment scale in Ethiopia. Scientific soil analysis is not an effective approach for SQ assessment in developing regions. An alternative option to evaluate using farmer knowledge is thus necessary but this can be sound after verified scientifically in the context of each region. The present study aims to evaluate SQ status (categories) identified by local farmers using scientific soil measurements, and assess their potential as indicators of soil degradation for decision making in the Mai-Negus catchment, northern Ethiopia. In this study, the scientifically measured soil attributes significantly differed (P ? 0.05) among the SQ categories identified by the local farmers. Using variables retained in the four identified component factors, discriminant analysis identified soil porosity to be the most powerful variable that can help discriminate the SQ status. The study shows that farmer derived SQ status (low, medium, high) could be crucial in providing basis for management and policy decision making as validated by analytical components. Therefore, attention should be given toward integrating farmer knowledge in SQ management to increase chance of technology adoption by farmers.